A modification of Shamir's Three-Pass protocol by implementing one-time pad algorithm / Nur Khairunnisa' Kusman, Nurul Hanis Abd Rashid and An Nur Ameera Zamani - Kusman, Nur Khairunnisa'; Abd Rashid, Nurul Hanis; Zamani, An Nur Ameera (2019)
Shamir's three-pass protocol is one of the methods that grants one party to send a message to another party without exchange any keys in the encryption and decryption process. However, the security in Shamir's three-pass protocol provided is insufficient due to the advanced technology. In order to improve security, a proper algorithm should be implemented in the three-pass protocol by adding phases at starting and ending of the process. Hence, the unbreakable one-time pad is proposed to implement in Shamir's three-pass protocol. The objectives of this study are to modified Shamir's three-pass protocol by implementing one¬ time pad protocol and to develop Graphical User Interface (GUI) by using Maple software. As a result, this study success to develop the algorithm by implemented one-time pad in Shamir's three-pass protocol. This can be proved when the result in the algebraic calculation is the same as the result in Maple which is the message get by the receiver is exactly same as the sender.